Carboidrases na alimentação de fêmeas suínas em lactação - Engelsing, Eliane Fátima Rocha (2024)
In total, two experiments were conducted. The first aimed to evaluate the effects of βmannanase supplementation in the presence of xylanase in diets with reduced metabolizable energy (ME). The second aimed to assess the effect of xylanase supplementation in diets containing 20% dried distillers grains with solubles (DDGS) on the zootechnical and productive performance, nutrient digestibility, milk chemical composition, and biochemical, hematological, and immunological blood profiles of lactating sows. Experiment I: A total of 60 Agroceres PIC sows (±248.40 kg initial weight; final weight 232.39 kg), with an average parity of 2.89, 2.60, and 2.70, respectively, for (DC0), (DC85), (DC100), were allocated in a randomized block design within three dietary treatments: (1) control diet containing only xylanase valued at 40 kcal of ME/kg (DC0); (2) DC0 + β-mannanase (3 g t-1 with a value of 45 kcal of ME/kg) (DC85); and (3) DC0 + β-mannanase (3 g kg-1 with a value of 60 kcal of ME/kg) (DC100). Sows fed the DC85 diet showed higher final body weight (FBW) than those fed DC100, with performance comparable to DC0. Sows fed the DC100 diet exhibited greater body weight loss (BWL) compared to DC85, similar to the DC0 diet. Regardless of the energy valuation in the diets, sows fed diets supplemented with β-mannanase had higher digestible protein. For digestible organic matter, sows fed the DC85 diet showed a higher value compared to the DC100 group, comparable to DC0. Digestible energy values were higher for the group that received the DC85 diet, matching the value of the DC0 diet when compared to DC100. The globulin variable presented a higher value for animals fed the DC0 diet compared to the DC100 diet. Regarding the hematological profile, there was an increase in mean corpuscular hemoglobin concentration in sows fed the DC85 diet compared to the others. Females fed the DC100 diet had a higher percentage of eosinophils compared to the other groups. Milk from females fed the DC0 diet had a higher percentage of lactose and fat-free dry extract compared to the milk from DC85, similar to the results of the DC100 group. Animals that received the DC100 diet had a higher concentration of immunoglobulin G compared to those that received the DC0 or DC85 diets. Supplementation with β-mannanase in diets containing xylanase allows for a reduction of 85 kcal of ME/kg, as it improved the female's body condition and the digestibility of protein, organic matter, and digestible energy without negatively affecting biochemical and hematological parameters, milk composition, or piglet performance. Experiment II: A total of 60 sows (Agroceres PIC) were randomly selected and allocated to two dietary treatments composed of a control diet with DDGS (DC, without xylanase enzyme) and a DC diet supplemented with xylanase (100 g/t of feed). The batch over time (round) was considered a blocking factor, and the sow in each pen was considered an experimental unit. The sows were classified by parity into three groups: 24 primiparous sows, 26 sows with 2 or 3 parities, and 10 sows with 4 or 5 parities, with weaning at 21 days of lactation, and an average parity of 2.05. The animals in the xylanase-fed group showed a higher albumin concentration (P = 0.009) compared to the DC group animals. There was no treatment effect on the other biochemical profile parameters. The animals fed the DC diet showed a higher red blood cell distribution width (P = 0.016), but there was no treatment effect for other hematological parameters. Xylanase supplementation resulted in a higher apparent crude protein digestibility coefficient (P = 0.012) and digestible protein value (P = 0.001). There was an increase in the fat percentage (P = 0.031) in the milk from sows that received diets containing the xylanase enzyme compared to those that received the control diet. Xylanase supplementation in diets containing 20% DDGS improved protein fraction digestibility and milk fat percentage without altering the zootechnical performance of the sows and their litters. There were no changes in the biochemical, hematological, and immunological blood parameters of the lactating sows.